Management accounting information systems quality’s impact on banking’s excellent corporate governance and banking performance in Indonesia - Susilawati, Christine Dwi Karya; Tin, Se; Setiana, Sinta; En, Tan Kwang (International Journal of Management and Sustainability, 2025)
This study aims to examine the impact of MAISQ on both GCG and banking performance within Indonesian banks. This research aims to address the low GCG practices in Indonesia compared to neighboring countries and investigate ways to enhance MAISQ in general, thereby enhancing Indonesian GCG and enhancing banking performance. Using SEM PLS, this research tested data gathered from 770 respondents from 260 Indonesian private banks. The respondents that make up the sample are marketing managers, accounting managers, and customer service representatives. This present study has analyzed the interrelationship amongst MAISQ and GCG on the performance of banking institutions. The present study finds that GCG has a significant positive effect on bank performance. Improved MAISQ leads to improved GCG practices for better banking performance. A satisfactory is fundamental in the practice of GCG for better banking performance. Thus, Indonesian banks are urged to enhance their management accounting systems toward improved governance and superior financial performance. Banks are encouraged to invest in sophisticated MAISQ toward better GCG practices. Policymakers are encouraged to encourage such a transition through regulations, incentives, and implementation of training programs to achieve the highest benefit from improved MAISQ.